Subjective Well-Being, Spirituality And Immunity of Islamic Lecturing Members When Facing The Covid-19 Pandemy - Asiyah, Siti Nur; Kumalasari, Mei Lina Fitri; Kusumawati, Estri (International Conference on Sustainable Health Promotion, 2021)
The covid-19 pandemic, which affects almost all of the world's population, not only disrupts human physical health due to its rapid and massive transmission. This fact also makes the panic and anxiety of all elements of society, even very disturbing economic stability that has been neatly arranged. The COVID - 19 pandemic has impacted to reduce immunity. One way to improve it is to improve spiritually. Spirituality such as meditation habits, praying, reading scriptures and conducting religious ritual activities can reduce emotional reactions to stress and cause relaxation. This study aims to determine the relationship of spirituality with immunity, subjective well-being with immunity as well as the relationship between spirituality and subjective well-being with immunity in Islamic lecturing members when facing pandemic COVID - 19. The subject of this study was the study congregation in several regions in Indonesia, amounting to 135 people. The sampling technique used was accidental sampling. Analysis of the data used is linear regression analysis. The results showed that the significance number p = 0.000 <0.005 and the correlation coefficient is 0.444. Thus it can be stated that there is a significant positive relationship between spirituality and subjective well-being with immunity